Integrative Genomic and Transcriptomic Analysis of Primary Malignant Gliomas Revealed Different Patterns Between Grades and Somatic Mutations Related to Glioblastoma Prognosis - Jin, Huawei; Yu, Zhenhua; Tian, Tian; Shen, Guoping; Chen, Weian; Fan, Miao; He, Qun; Dai, Dandan; Zhang, Xuan; Liu, Dawei (Frontiers in Molecular Biosciences, 2022)
Background: As reflected in WHO classification of glioma since 2020, genomic information has been an important criterion in addition to histology for glioma classification. There is significant inter-grade difference as well as intra-grade difference of survival probability among glioma patients. Except the molecular criteria used in WHO classification, few studies have explored other genomic factors that may be underlying these survival differences, especially in Chinese populations. Here we used integrative genomic approaches to characterize a Chinese glioma cohort to search for potential prognostic biomarkers. Methods: We recruited 46 Chinese patients with primary malignant glioma. All the patients were analyzed with whole-exome sequencing (WES) and 27 of them were analyzed with RNA-seq. We compared the molecular features between patients in different WHO grades. We classified the glioblastoma (GBM) patients into two groups (good vs poor survival) using six-month progression-free survival (PFS6) status, and compared the genomic profiles between two groups. Results: We found grade II and grade III patients cluster together (LGG) and they are different from GBM in unsupervised clustering analysis with RNA-seq data. Gene set enrichment analysis (GSEA) comparing GBM and the LGG group suggested GBM had upregulation of multiple pathways related to genome integrity and immune cell infiltration. Further comparison of somatic mutations between the two groups revealed TOPAZ1 as a novel mutation associated with GBM and prevalence of CNV in multiple genes in GBM. Comparison between PFS6 good and poor GBM patients revealed six genes (TRIML2, ROCK1, PKD1, OBSCN, HECTD4 and ADCY7) were significant mutated and two genes (NTRK1, B2M) had more CNV alterations in the poor prognosis group. Conclusions: Taken together, our molecular data revealed that GBM patient showed distinct characteristics related to individual gene, chromosome integrity, and infiltrating immune cells compared to LGG (grade II/III) patients. We also identified few novel genes with SNV or CNV which might be the potential markers for clinical outcome of GBM.